Occurrence of ochratoxin A in Astragalus propinquus root and its transfer to decoction - Toman, Jakub; Ostry, Vladimir; Grosse, Yann; Roubal, Tomas; Malir, Frantisek (Mycotoxin research, 2018)
The aim of this study was to conduct a survey assessing (a) the ochratoxin A (OTA) content in different samples of Astragalus propinquus root (AR), one of the fundamental herbs in traditional Chinese medicine, and (b) the rate of OTA transfer to AR decoctions that are traditionally used to reduce general weakness and increase overall vitality. A validated method of high-performance liquid chromatography with fluorescence detection (HPLC-FLD) was used to determine OTA concentrations in AR samples and AR decoctions. The limit of quantification was 0.35 ng/g; the recovery of the HPLC method for AR samples was 82%; and the relative standard deviation (SD) of repeatability was 2.6%. All 40 tested AR samples were positive, with a mean value of 451.0 ng/g (range, 28.8-1700.0 ng/g). The transfer rate of OTA to decoctions, from a naturally contaminated and homogenized AR sample (internal reference material) with a concentration of OTA of 288.9 ng/g ± 12.3 (SD), was 83.4% ± 8.5 (SD). We believe it is necessary to continue OTA monitoring in AR and other herbal products, estimate the actual human usual intake, and perform health risk assessment.
Keywords: Ochratoxin A; Fluorometry; Herbal food supplement; léky rostlinné čínské; Astragalus propinquus; Chromatography, High Pressure Liquid; fluorometrie; Herbal products; Astragalus propinquus Schischkin; vysokoúčinná kapalinová chromatografie; kontaminace potravin; Humans; Food Contamination; HPLC-FLD; ochratoxiny; Drugs, Chinese Herbal; Traditional Chinese medicine; lidé; Ochratoxins